Implementation of a Triple Bottom Line Based Sustainability Strategy: Case Study of PT Multi Bintang Indonesia Tbk - Napitupulu, Ucok Pardamean; Riwayati, Hedwigis Esti (Journal Research of Social Science, Economics, and Management, 2026)
In the face of growing global environmental concerns and increased demand for socially responsible corporate practices, sustainability has emerged as a key aspect of corporate governance. Companies are increasingly expected to not only deliver profits but also contribute positively to environmental preservation (planet) and social welfare (people). PT Multi Bintang Indonesia Tbk, as a major player in the Indonesian beverage industry, faces substantial challenges related to environmental impact, regulatory compliance, and evolving market preferences. This research aims to analyze the implementation of a Triple Bottom Line based sustainability strategy at PT Multi Bintang Indonesia Tbk from a strategic management perspective. This study uses a descriptive qualitative approach with triangulation techniques through in-depth interviews, observation and document review. The analysis was carried out using the Internal Factor Evaluation, External Factor Evaluation framework, and SWOT analysis to identify internal and external factors that influence the success of sustainability strategies. The research results show that the implementation of Triple Button Line is integrated into company operations through non-alcohol product innovation (profit), community empowerment and employee development programs (people), as well as resource efficiency and waste management (planet). The findings also reveal that there is alignment between the company’s sustainability strategy and the regulations of the Financial Services Authority, especially POJK No. 51/2017. This research makes a contribution by integrating the TBL approach into a strategic analysis framework, which is still limited in previous literature.